Templer and the Road to Malayan Independence: The Man and His Time, by Leon Comber, Singapore: ISEAS, 2015, 239 pp. - Abu Talib Ahmad, (Kajian Malaysia, 2016)
There are a number of books on General Sir Gerald Templer and his two year proconsulship in Malaya (1952–1954) as High Commissioner and Director of Operations but views on the man are somewhat mixed. One view describes him as a "martinet in manner and appearance"; another labeled him a dictator while a Malaysian scholar claimed the man was notorious for his violent temper and intemperate language. Then there are those who saw his crucial role in defeating the Communist uprising while others credited this success to the Briggs Plan which was put in place before his arrival in Malaya by the previous Director of Operations Lt. General Sir Harold Briggs. This brilliant plan forced the Malayan Communist Party (MCP) to focus on consolidation rather than military offensive through its withdrawal deep into the Malaya-Thai border and later into south Thailand.